2008
DOI: 10.1007/s11205-008-9336-2
|View full text |Cite
|
Sign up to set email alerts
|

Health, Quality of Care and Quality of Life: A Case of Frail Older Adults

Abstract: Life satisfaction, Client satisfaction, Case management service, Mediating effect,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Statistically significant associations between QoC and HRQoL is an important finding and has been reported by similar studies in pediatric [4] and geriatric populations [15]. High QoC provision to pediatric patients is one of the largest determinants of improved parental perceptions about their child's HRQOL [5].…”
Section: Discussionmentioning
confidence: 92%
“…Statistically significant associations between QoC and HRQoL is an important finding and has been reported by similar studies in pediatric [4] and geriatric populations [15]. High QoC provision to pediatric patients is one of the largest determinants of improved parental perceptions about their child's HRQOL [5].…”
Section: Discussionmentioning
confidence: 92%
“…Thus, this study examined three important factors: injury, medication error, and resident satisfaction. Evidence suggests a strong association between quality of care and quality of life mediated by health satisfaction (Hsieh, 2009). Certainly, older adults need social support whether living inside or outside an elder home.…”
Section: Complaints (Resident Satisfaction)mentioning
confidence: 99%
“…Case "As Needed" Case Management 275 management is linked to positive outcomes, such as satisfaction with case management services being directly associated with quality of life for "frail" older adults (Hsieh, 2009). Sargent and colleagues (2007) found that older adults reported that case management helped reduce stress, improve mood, and increased coping ability, and that their caregivers reported receiving emotional support.…”
Section: The Growing Evidence-base For Case Managementmentioning
confidence: 99%
“…Yet, a lack of clarity about how and where case management should be delivered persists and could hinder aging services' ability to implement the new models supported through the PPACA. Research on case management is limited to describing the roles of case managers (Kelsey & Laditka, 2009), the psychosocial needs of clients (Ferry & Abramson, 2006), and the outcomes achieved (Gensichen et al, 2005;Hsieh, 2009;Sargent, Pickard, Sheaff, & Boaden, 2007), rather than its use and application across service settings. Given that case management's episodic process can vary from high intensity to a standby mode within the same service network (Carrier, 2012) and may vary from general to disease-specific focuses, our study examines how aging services may use existing case management practices in general and through integrated models of care for depression.…”
mentioning
confidence: 99%